The impact of mining foreign direct investment on economic growth in Ghana - Anthony Ennin; Emmanuel Agyapong Wiafe (Cogent Economics & Finance, 2023)
This paper investigates the impact of mining foreign direct investment on economic growth in Ghana using quarterly time series data from 1996-2015. The study employs the Autoregressive Distributed Lag bounds testing approach to cointegration and the error correction model to investigate the existence of a long-run and short-run equilibrium relationship between foreign direct investment into the mining sector and economic growth. The study established that foreign direct investment into the mining sector hurts economic growth in Ghana in the long run but a positive in the short run. The study also finds that private sector credit, capital stock, government spending, and labour participation rate have a statistically significant positive relationship with economic growth in the long run. Trade openness exhibited a statistically significant negative long-run relationship with economic growth, while inflation had a positive but insignificant impact on economic growth for the study period. The study recommends that government should encourage research and development in the mining sector and align mining and other environmental policies to ensure sustainable growth. It is further recommended that government tactfully provide investment incentives to ensure the development of other sectors to avoid the Dutch disease.
Keywords: 330; ARDL; Ghana; economic growth; cointegration; FDI-growth nexus; mining FDI